ANALYSIS OF SISBRO REGISTRATION SERVICES (OUTPATIENT ONLINE BOOKING SYSTEM) ON SISBRO USER SATISFACTION AT THE MEDICAL REHABILITATION INSTALLATION POLY OF GAMBIRAN HOSPITAL: English - Nazahah Tahta Afida; Ardi Bastian (Journal of Hospital Management and Services, 2025)
Waiting time is one of the indicators of service quality that can have an impact on patient satisfaction. SIBRO can be used to facilitate online outpatient registration so as to increase patient satisfaction. The purpose of analyzing the SISBRO (Outpatient Online Booking System) registration service on the satisfaction of SISBRO users at the rehabilitation installation poly of Gambiran Kediri Hospital. Quantitative research design with a cross sectional approach conducted at the hospital. Gambiran Kediri in May-June 2024. The study population was all poly patients of the outpatient Medical Rehabilitation Installation at Gambiran Hospital who used SISBRO with a sample of 148 respondents using purposive sampling. Variables of SISBRO (Outpatient Online Booking System) registration services and satisfaction with SISBRO use. Data collection using questionnaires was analyzed using a simple linear regression test. The results of the study showed that the SIBRO registration service variable had significance (p-value 0.000), a strong relationship (0.987) and contributed 97.4% to SIBRO user satisfaction. There is a strong influence between registration services on the satisfaction of using SIBRO so that hospitals need to update the system and socialize to users to increase SIBRO user satisfaction.